2015
DOI: 10.4317/medoral.20613
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors on periapical surgery: A systematic review

Abstract: BackgroundAnalyze the most important prognostic factors when performing periapical surgery and compare the success rates of distinct authors.IntroductionPeriapical surgery is an approach to treat non-healing periapical lesions and it should be viewed as an extension of endodontic treatment and not as a separate entity.Material and MethodsA search of articles published in Cochrane, PubMed (MEDLINE) and Scopus was conducted with the key words “prognostic factors”, “prognosis”, “periapical surgery”, “endodontic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 23 publications
2
31
0
3
Order By: Relevance
“…, Serrano‐Giménez et al . ). Two systematic reviews and meta‐analyses reported that the type of root‐end filling material (MTA, IRM, SuperEBA) had no significant influence on treatment outcome (Tsesis et al .…”
Section: Bioactive Endodontic Cements As Root‐end Filling Materialsmentioning
confidence: 97%
“…, Serrano‐Giménez et al . ). Two systematic reviews and meta‐analyses reported that the type of root‐end filling material (MTA, IRM, SuperEBA) had no significant influence on treatment outcome (Tsesis et al .…”
Section: Bioactive Endodontic Cements As Root‐end Filling Materialsmentioning
confidence: 97%
“…Calcium hydroxide medicament (RC Cal, Prime Dental Products, India) was placed thrice for a period of 1 week each. As the root canals exhibited persistent discharge of exudates and due to two prognostic factors (size of the lesion which was more than 10 mm and the thinning or destruction of the palatal bone) which were unfavourable for this case [9], periapical surgery was planned following the recommendation given by the Spanish Society of Oral Surgery (point 3: a radiotransparent lesion measuring over 8 to 10 mm in diameter).…”
Section: Case Presentationmentioning
confidence: 99%
“…Three such studies involving very low risk of bias [ 15 17 ] have reported success rates of 85-94.3% with the use of MTA. A meta-analysis published by Von Arx et al [ 18 ] and a systematic review by Serrano-Giménez et al [ 19 ] have defined MTA as the material of choice for retrograde cavity sealing in periapical surgery.…”
Section: Discussionmentioning
confidence: 99%